Pengaruh Pendapatan Mudharabah Dan Musyarakah Terhadap Profitabilitas (ROA) Bank Syariah Mandiri Periode 2015-2020 - Firdaus Ananta Ababiel; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the effect of Mudharabah Income and Musyarakah Income on Profitability (ROA) at Mandiri Syariah Banks listed on the Indonesia Stock Exchange. The object of this research is Bank Syariah Mandiri on the Indonesia Stock Exchange. The samples in this study were 6 samples obtained from the financial statements of Bank Syariah Mandiri for the period 2015 to 2020 using a saturated sampling technique. From the research results using the coefficient of determination test (R Square) the results obtained are 94.8% Mudharabah Income and Musyarakah Income jointly affect Profitability, while the remaining 5.2% is influenced by other factors not examined, for example FDR, NFR, Inflation and others. Based on the results of the t (partial) test for the Mudharabah Income variable, it was obtained sig 0.105 > 0.05 and the calculated t value of Mudharabah Income was -2.296 <t table 3.18 so it can be concluded that Mudharabah Income has no effect on Profitability. Musyarakah income obtained sig 0.068 > 0.05 and the t value of Musyarakah income is 2.794 <t table 3.18 so it can be concluded that Musyarakah income has no effect on profitability. And from the F test (simultaneous) obtained sig 0.012 <0.05 and Fcount 27.294 > Ftable 3.28, it can be concluded that Mudharabah Income and Musyarakah Income simultaneously influence the Profitability of Mandiri Syariah Banks Listed on the Indonesia Stock Exchange.